Role Of Amusement Park In Value Addition To The Tourist Place: Case Study Of Chail, H.P. (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Tourism is a social, cultural and economic phenomenon which entails  the movement of people to countries or places outside their usual environment for  personal or business/ professional purposes. Tourism helps to assimilate culture and  social bondage. Theme parks and amusement parks are very good tourist attractions.  An amusement park is a combination of thrill rides, roller coaster rides, family rides,  water attractions or rides in darkness in a covered train. Chail, a tourist destination in  H.P is one of the popular tourist destinations. Opening an amusement park will help  to attract more tourists. Objective: To identify the feasibility of opening a Amusement  park in Chail, H.P. Methodology: The research instrument used was a questionnaire was  30 tourists visiting Chail. Results: Around 86% of the tourist population agreed that  provision of Amusement Park would give opportunity to development of Chail and of  the state overall. 76% agreed Amusement Park will be a value addition to Chail and  help in the economic and financial upliftment of the state. Conclusion: Value addition  of Amusement Park in tourist places would help in social and cultural development of  the state. Such leisure activity acts as strong magnet for tourism industry.
Keywords: Tourism; Amusement park; Theme parks; Chail